“Delinquents Often Become Criminals”:: Juvenile Delinquency in Halifax, 1918-1935 - Boudreau, Michael (Acadiensis, 2010)
Abstract During the early part of the 20th century, juvenile delinquency in Halifax was perceived to be a serious social and moral problem that had to be solved without delay. Consequently, between 1918 and 1935, many of Halifax’s criminal justice officials fully embraced most facets of Canada’s modern juvenile justice system in order to deal with the local juvenile delinquents. By utilizing this new regulatory regime (notably the juvenile court and probation) to grapple with juvenile delinquency, Halifax was in the forefront, along with other cities, of the efforts to regulate and criminalize the lives of primarily poor, working-class children and their families.